Does modified Otago Exercise Program improves balance in older people? A systematic review - Anabela Correia Martins; Cláudia Santos; Catarina Silva; Daniela Baltazar; Juliana Moreira; Nuno Tavares (Preventive Medicine Reports, 2018)
Exercise interventions focused on strength and balance are effective for falls prevention in older people, however compliance to exercise is often a problem. Tailored intervention programs are recommended to meet the person preferences and increase compliance. Otago Exercise Program (OEP) is the most disseminated fall prevention program and is individually prescribed at home. The purpose of this study was to identify OEP modified formats and investigate their effects on balance when compared to its original form of delivering.Four electronic databases were searched, PubMed, PEDro, Science Direct and Scopus, between January and February 2017. Eligibility criteria included experimental or qualitative design studies conducted among older adults (≥50 years) at risk of falling, ongoing exercise interventions with modified formats of OEP. The primary outcome was balance. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were used.Eight studies met the inclusion criteria, five were randomized controlled trials (RCTs), two were quasi-experimental and one was a qualitative study. Therefore, a qualitative analysis was performed. Modified formats of OEP included additional vestibular or multisensory balance exercises, augmented reality, exercise in group and a DVD delivering format (in group or individual). In general, all studies using OEP modified formats reported improvements on balance and functional ability. However, it remains unclear if it is as effective as the original OEP and which modified format is more effective. Keywords: Otago Exercise Program, Community-dwelling older adults, Balance, Personalized exercise